Artikulasi fikih kesehatan dalam kebijakan kesehatan global: Serba-serbi bahasa hadits terhadap ilmu kesehatan islam - Ishaq, Ala; T, akmal Nurrosyidin; Romadhani, Septa Widyanti; Elfadiny, Keysha Ananda (Maliki Interdisciplinary Journal, 2025)
Hadith, as the second primary source of Islamic law after the Qur’an, plays a significant role in shaping the worldview of Muslims, particularly in maintaining physical and spiritual health. This study aims to examine the health-related values contained in the Prophet Muhammad’s hadiths and to explore their relevance to modern medical principles. Using a descriptive qualitative approach, this paper analyzes various hadiths that emphasize cleanliness, healthy living, and the balance between physical and spiritual well-being. The findings indicate that Islam places cleanliness and health as integral aspects of faith, encompassing the purification of the body, environment, and soul. The health principles derived from hadiths are consistent with modern medical concepts, such as hand hygiene, environmental cleanliness, and maintaining a balanced diet. Therefore, the hadiths of the Prophet not only serve as spiritual guidance but also as a scientific foundation relevant to improving public health and well-being.